ANALISIS PENGARUH MODAL PSIKOLOGIS KARYAWAN (PSYCHOLOGICAL CAPITAL) TERHADAP KEINGINAN UNTUK KELUAR (TURNOVER INTENTION) DENGAN TINGKAT STRES KERJA (WORKPLACE STRESS) SEBAGAI VARIABEL INTERVENING (Studi Pada Karyawan PT. Sandang Asia Maju Abadi Semarang) - Fadinalisa Damayanti; Suharnomo Suharnomo (Diponegoro Journal of Management, 2023)
ABSTRACT This study aims to analyze the effect of work stress on turnover intention with This study aims to analyze "Analysis of the Effect of Psychological Capital of Employees (Psychological Capital) on Desire to Leave (Turnover Intention) with Workplace Stress Levels as Intervening Variables" (Study on Employees of PT. Sandang Asia Maju Abadi Semarang). This study uses psychological capital as the independent variable, turnover intention as the dependent variable, and workplace stress as the intervening variable. The population in this study were active production employees of PT Sandang Asia Maju Abadi Semarang, totaling 2,357 people. The sample in this study used a non-random sampling technique with a total of 99 respondents. The data obtained from the questionnaires were processed and analyzed using the SmartPLS program. The results of the study show that Psychological Capital has a negative effect on turnover intention and is rejected. There is another factor, namely based on the last education of the respondent so that the answer given by the respondent is not correct or not relevant to the research question. Research also shows that there is a negative and significant relationship between Psychological Capital and rejected job stress. This can also happen due to other factors as well, namely based on the respondent's last education so that the answers given by the respondents are inaccurate or irrelevant to the research question. Other results show that Workplace Stress has a positive and significant effect on turnover intention. While the results of the mediating variable, namely Workplace Stress, succeeded in becoming a mediating variable between Psychological Capital and Employee Turnover Intention.